The Implementation of 2013 Curriculum in English Teaching Learning at MAN 1 Pekalongan - Noviawati, Nita (Department of English Language Education, UIN Sunan Ampel Surabaya, 2017)
This research was conducted with the aim to know and describe the implementation of 2013 curriculum in English teaching-learning at MAN 1 Pekalongan. Things done in this study include the implementation of teaching and learning activities, including constraints and actions related to teaching and learning activities at MAN 1 Pekalongan. The method used in this study is a case study on English teaching-learning by using 2013 curriculum at MAN 1 Pekalongan. The sample and place of research used in this study is an eleventh class, especially eleventh social 4class at MAN 1 Pekalongan.The source of data obtained by 1)Teaching-learning process by using 2013 curriculum; 2) The information involving the teacher and the students; 3)The documentation related to the implementation of 2013 curriculum. The results of this research can be concluded that many obstacles in the implementation of 2013 curriculum, such as the limited time on English teaching and learning activities, the facilities and infrastructure, and the assessment.